Teaching Politics and International Relations - Alexandra Mihai (Journal of Contemporary European Research, 2014)
A valuable state-of-the-discipline overview and a handbook for academics at all stages in their career. The collection aims to contribute to enriching the Politics curriculum design and to encourage the adoption of innovative pedagogical techniques.